The performance and ranking pattern of PV systems incorporated with solar trackers in the northern hemisphere - Bahrami, Arian; Okoye, Chiemeka Onyeka (Pergamon-Elsevier Science Ltd, 2018)
Energy produced from a typical PV panel with or without solar tracker is mainly dependent on the available solar irradiance. Interestingly, for some locations on nearly the same latitude in the northern hemisphere, the solar irradiance varies significantly resulting to change in the ranking pattern of solar PV trackers. For this reason, the present study aims to explore the effect of solar irradiation on the technical and economic performance of PV panels incorporated with different solar trackers. Particularly, this paper focuses on locations classified as medium and high latitude countries (20-70 degrees N) in the northern hemisphere. While the considered locations in the northern hemisphere cover the continent of Europe, Africa, Asia, and North America, the studied solar trackers include dual/full/2-axis and single/one-axis (with several tracking orientations namely; East-West, North-South, Inclined East-West, and Vertical-Axis) trackers. The performance metric indicators of the energy gain and levelized cost of electricity (LCOE) are utilized to depict the most preferred solar tracking option for implementation in those regions. Overall, the observed ranking patterns are expected to guide not only solar PV project designers and engineers but also policymakers in the selection and implementation of suitable trackers in the regions.
Keywords: Solar irradiation; PV system; Solar trackers; Performance ranking; Northern hemisphere